2007
DOI: 10.1021/la700856a
|View full text |Cite
|
Sign up to set email alerts
|

Probing Chitosan and Phospholipid Interactions Using Langmuir and Langmuir−Blodgett Films as Cell Membrane Models

Abstract: The interaction between chitosan and Langmuir and Langmuir-Blodgett (LB) films of dimyristoyl phosphatidic acid (DMPA) is investigated, with the films serving as simplified cell membrane models. At the air-water interface, chitosan modulates the structural properties of DMPA monolayers, causing expansion and decreasing the monolayer elasticity. As the surface pressure increased, some chitosan molecules remained at the interface, but others were expelled. Chitosan could be transferred onto solid supports alongs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
0
15

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 50 publications
14
110
0
15
Order By: Relevance
“…Therefore, hydrophobic forces are likely to play an important role, in accordance with our previous results [25][26][27][28] and with the literature [31,32]. Indeed, Krajewska et al [31,32] have shown that non-electrostatic contributions are relevant for chitosan interaction with DPPC, DPPG and cholesterol monolayers in measurements where pH and temperature changes were studied.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, hydrophobic forces are likely to play an important role, in accordance with our previous results [25][26][27][28] and with the literature [31,32]. Indeed, Krajewska et al [31,32] have shown that non-electrostatic contributions are relevant for chitosan interaction with DPPC, DPPG and cholesterol monolayers in measurements where pH and temperature changes were studied.…”
Section: Resultssupporting
confidence: 91%
“…A comparison of the activities from distinct samples of chitosan indicates, however, that non-electrostatic interactions also play an important role [25,26]. Indeed, the importance of these types of interactions has been demonstrated at the molecular level in studies with model membranes [23,[25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMPA is one of the most used phospholipids in this context owing to its suitability to deposit multilayers [131,132]. Examples include studies of a mucin protein in LB films of DMPA, where chitosan was able to gradually remove the protein, according to FTIR measurements [116] and interaction studies between DMPA and the protein-polysaccharide complex extracted from the mushroom Agaricus blazei Murill [133].…”
Section: Films Deposited On Solid Substratesmentioning
confidence: 99%
“…Incidentally, the Langmuir-Blodgett technique is useful in the study of molecular-level interactions, in addition to allowing for assembling nanomaterials for sensors and optical and electronic devices [40,41]. Chitosan was able to expand and penetrate phospholipid Langmuir monolayers [42][43][44][45]. Two main representative phospholipids used were phosphatidylglycerol and phosphatidylcholine to mimic bacterial and mammalian membranes [46][47][48], respectively.…”
Section: Introductionmentioning
confidence: 99%